Integrative analysis of the metabolome and transcriptome provides insights into the mechanisms of amino acids and their derivatives biosynthesis in Polygonatum - Xiuzhi Wang; Lingjun Cui; Qiang Xiao (PLoS ONE, 2025)
The composition and concentration of amino acids and their derivatives in Polygonatum are crucial factors that indicate its nutritional value and have a substantial impact on its potential for market development as a medicinal and edible plant. This study utilized comprehensive targeted metabolomics detection, transcriptome analysis, and weighted gene co-expression network analysis (WGCNA) to assess the quality characteristics of amino acids and their derivatives. Additionally, it aimed to investigate the pivotal genes that influence the synthesis of these compounds. The analysis revealed that there was a total of 72 distinct amino acids and their derivatives present in both forms of Polygonatum. Furthermore, there were notable variations in the content of 37 of these amino acids. A total of 271 genes are responsible for encoding 37 enzymes that are involved in the production of amino acids and their derivatives. The WGCNA clustering analysis, along with the metabolic profile of amino acids and their derivatives and transcriptome analysis, categorized the transcripts into six modules. Among these modules, the active components of amino acids and their derivatives showed a positive correlation with the MEturquoise and MEblue modules. This correlation helped identify 10 key genes that are highly likely to influence the synthesis of amino acids and their derivatives. Therefore, we validated these results using qRT-PCR. The modulation of the expression patterns of these crucial genes can establish a theoretical foundation for the subsequent breeding of Polygonatum germplasm with abundant amino acid content and diversity.